CT Fishing Report Occurrences - Hedreen, Rebecca; Grace, Sean (Zenodo, 2021)
Dataset of gamefish occurrences as compiled from the Connecticut Fishing Report (2006-2018) and Trophy Fish Report (2009-2018), both published by the Connecticut Department of Energy and Environmental Protection. Compiled as thesis project by Rebecca Hedreen for a Masters of Science in Biology from Southern Connecticut State University, with advisor Dr. Sean Grace.
Keywords: Connecticut; Long Island Sound; coastal fisheries; data collections; dept.bio; dept.lib; estuarine fisheries; fish catch statistics; game fish; geographical coordinates; geographical distribution; sport fishing statistics

Miki Gets Dressed Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl, 2021)
Keywords: dept.lib

Sharing: A Pull-the-Tab Book Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Pull and Play: Pacifier Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

SURPRISE! Slide and Play Shapes Translated by Wendeline Hardenberg - Fouquier, Elsa (Twirl, 2021)
Keywords: dept.lib

Animal Friends 1 2 3 Translated by Wendeline Hardenberg - Loupy, Christopher (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Rain Forest Animals Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2021)
Keywords: dept.lib

The Pop-Up Guide: Space Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl, 2021)
Keywords: dept.lib

Little Bug on the Move Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Matching Game Book: Bugs and Other Little Critters Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Dinosaurs and the Prehistoric World Translated by Wendeline Hardenberg - Hedelin, Pascale (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Oceans and Marine Life Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Polar Animals Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2021)
Keywords: dept.lib

Mr. Lion's New Hair! Translated by Wendeline Hardenberg - Teckentrup, Britta (Twirl, 2021)
Keywords: dept.lib

Magnetology: Animals Translated by Wendeline Hardenberg - Poulain, Maud (Twirl, 2021)
Keywords: dept.lib

The Pop-Up Guide: Vehicles Translated by Wendeline Hardenberg - Poulain, Maud (Twirl, 2021)
Keywords: dept.lib

This Book Can Do Anything Translated by Wendeline Hardenberg - Mory, Tristan (Twirl, 2021)
Keywords: dept.lib

Pull and Play Books: Let's Be Safe Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Vehicles and Transportation Translation by Wendeline Hardenberg - Hardenberg, Wendeline A. (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Space and Sky Translated by Wendeline Hardenberg - Hardenberg, Wendeline A. (Twirl, 2021)
Keywords: dept.lib

The Bookshop of Forgotten Dreams: A page-turning opposites attract romantic comedy! Translated By Wendeline Hardenberg - Blaine, Emily (One More Chapter, 2021)
Keywords: dept.lib

From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg - Aubry, Gwenaëlle (Columbia Journal, 2021)
From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg
Keywords: dept.lib

Expanding and Improving Our Library’s Virtual Chat Service: Discovering Best Practices When Demand Increases - Fruehan, Parker; Hellyar, Diana (Information Technology and Libraries, 2021)
With the onset of the COVID-19 pandemic and the ensuing shutdown of the library building for several months, there was a sudden need to adjust how the Hilton C. Buley Library at Southern Connecticut State University (SCSU) delivered its services. Overnight, the library’s virtual chat service went from a convenient way to reach a librarian to the primary method by which library patrons contacted the library for help. In this article, the authors will discuss what was learned during this time and how the service has been adjusted to meet user needs. Best practices and future improvements will be discussed.
Keywords: dept.lib; peer-reviewed